Functional Outcomes of Patella Fractures Treated With Anterior Plate Osteosynthesis at One Year. Issue 1 (January 2021) - Shymon, Stephen J.; Jansson, Hayley; Schneiderman, Brian A.; Nazareth, Alexander; Hoshino, Christopher Max; Zinar, Daniel M.; Gold, Stuart M.
Abstract : Objectives: To evaluate the functional outcomes of patients with displaced patellar fractures treated with anterior plate constructs. Design: Prospective cohort and retrospective clinical and radiographic assessment. Setting: Level I Trauma Center. Patients/Participants: Between 2014 and 2018, 18 patients who underwent operative intervention for an isolated, displaced patella fracture (OTA/AO 34C1-3) with a minimum of 1-year follow-up agreed to participate in the study. The mean follow-up was 19.5 ± 6.0 months. Intervention: Patients were treated with 2.4 or 2.7-mm plates and supplemental screws or cerclage wires. Main Outcome Measurements: Patients were evaluated with the Short Form-36 Survey and the Knee Injury and Osteoarthritis Outcome Scores and asked about symptomatic implants. The range of motion was assessed by goniometer. Results: The cohort had no wound complications, infections, nonunion, loss of reduction, or implant failure. Active knee flexion was 131 ± 7 degrees. Five patients (28%) endorsed implant irritation. Only one patient (5.5%) underwent implant removal, which consisted of transverse screw removal alone. Twelve of the 14 patients (86%), who were previously employed, returned to work at 10 ± 7 weeks. All Knee Injury and Osteoarthritis Outcome Scores subscale scores and the Short Form-36 Survey scores for physical functioning, limitations due to physical health, limitations due to mental health, and social functioning were significantly lower than reference population norms ( P < 0.05). Conclusions: Anterior plating provides reliable fixation for displaced patellar fractures and results in a low incidence of implant irritation. However, patients who had anterior fixation for displaced patella fractures continue to exhibit functional deficits at 1-year postoperatively. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.